“Verba volant, scripta manent”: desvendando Annunciada Chaves por meio de seus escritos (1915-2006) - COSTA, Elisangela Silva da (Universidade Federal do Pará, 2025)
The Bibliographic heritage represents a vast field of study to be explored in academia, and so this research aims to investigate the bio-bibliographical trajectory of the intellectual from Pará, Maria Annunciada Ramos Chaves, through the traces she left in her private library. It is characterized as a biographical research, of the bibliographic and documentary type. It was found that the collection analyzed contains: official and personal documents, books, magazines, photographs, postcards, programs of plays, newspaper clippings, legislation on teaching and various notes - which allow mapping and constructing aspects of the teaching of History between the 1930s and 1990s. The investigation focused on understanding the action of this protagonist for the promotion of the teaching of History analyzed from the perspective of the Cultural History, at regional and national levels. Dialogues within the scope of studies on bibliographic heritage, collecting and bibliophilia are also considered, through the analysis of the instances that guard and characterize a personal collection as a cultural asset. It was found that Professor Annunciada Chaves, despite not being a historian by training, created institutions, became a professional and developed several activities that helped to enhance the teaching of History in Pará. Annunciada Chaves identified herself as an intellectual mediator; she was a jurist, teacher, historian, manager and held positions in cultural and educational institutions that gave her a prominent place in a social network of intellectuals of local, national and international relevance, as stated in the dedications in her books. The content of her personal library, the object of study of this thesis, was configured as a historical-educational legacy whose books and the dedications contained in them operate as agents and witnesses.